IMPLEMENTATION OF WORDWALL LEARNING MEDIA ON THE LEARNING OUTCOMES OF CLASS VIII STUDENTS ON THE MATERIAL OF GROWTH AND DEVELOPMENT AT BINTANG LANGKAT JUNIOR HIGH SCHOOL - Anggraini, Dini Puji; Purba, Azrina (Universitas Negeri Medan, 2025)
Low student learning outcomes are a common problem at the end of the learning process. Suboptimal use of learning media is one of the causes of low student learning outcomes. This study was conducted with the aim of determining the extent to which the use of Wordwall learning media affects the learning outcomes of class VIII students at SMP Bintang Langkat. This study used a quantitative approach with the Quasi Experiment method. The research population was all eighth-grade students. The sampling technique was carried out using a purposive sampling method. The sample group was divided into two classes, namely the control class taught conventionally and the experimental class taught with wordwall media. Each class will be given a pretest and posttest. The instrument used was a multiple-choice test instrument with 20 questions on the material of growth and development. Before testing the hypothesis, the data were tested for normality and homogeneity. From the analysis results, it was obtained that the sample was normally distributed and categorized as homogeneous. Furthermore, a statistical hypothesis test can be carried out using the t-test. The results of the hypothesis test with the t-test showed that the calculated t-value was greater than the t-table so that Ho was rejected. This means that there is an effect of the use of the discovery learning model on the learning outcomes of students at SMP Bintang Langkat.